INFLUENCE OF CULTURAL ORIENTATION ON PERCEIVED ORGANIZATIONAL CREATIVITY CLIMATE: AN EXPLORATORY STUDY OF TWO STEEL PLANTS IN MALAYSIA - Hazman Shah Abdullah,; Razmi Chik,; Rahman Deen, (Asian Academy of Management Journal, 2006)
The study explores the relationship between cultural values and perceptions of the creativity climate. Asian culture is allegedly inimical to creativity and innovation in organizations. High power distance, high femininity, and greater orientation towards collectivity are discordant with the cultural underpinnings of the flatter, fluid, less formal, and networked organization. One hundred and seventy executives and nonexecutives of two steel mills were tested for the value orientation using an adaptation of Hofstede's measures for values and Ekvall's Creativity Climate Questionnaire for assessing the creativity climate of the organization. The executives' perceptions of the creativity climate in the organization were low and coincided only weakly with their value orientation. However, power distance and uncertainty avoidance stood out as the single most influential variable in creativity perceptions. Attention must be paid to the relationship and steps to ameliorate these influences by cultural profiling – a move that identify subcultures whose values may be more amenable to innovation and creativity than most.